Cerebrovascular hemodynamics in fetuses with congenital heart disease. Issue 12 (29th December 2017) - Man, Tingting; He, Yihua; Zhao, Ying; Sun, Lin; Liu, Xiaowei; Ge, Shuping
Abstract : Background and Objective: It is hypothesized that diminished cerebral vascular resistance or the "brain sparing effect" is associated with fetuses with complex congenital heart defects (CHD) and may affect their neurodevelopmental outcome. An alternative explanation is that it is related to the location, cardiac output, pressure, and resistance in left heart obstructive CHDs. We sought to determine the effects of various left and right heart obstructive defects on the cerebral and placental hemodynamics and to evaluate the utility of these variables for the assessment and prognosis of CHDs. Methods: A total of 290 fetal echocardiograms were reviewed, including 91 fetuses with CHD and 199 normal ones. The CHD fetuses were divided into four groups, that is, left‐sided obstructive lesions (LSOL), hypoplastic left heart syndrome (HLHS), right‐sided obstructive lesions (RSOL), and hypoplastic right heart syndrome (HRHS). The pulsatility index of middle cerebral artery (MCA‐PI) and umbilical artery (UA‐PI) were measured by pulse‐wave Doppler, and their Z scores were also derived. Cerebroplacental ratio (CPR) was calculated as: CPR=MCA‐PI/UA‐PI. Results: There was no significant difference in MCA‐PI between the 4 CHD and normal control groups ( P >.05). However, MCA‐PI and Z score decreased in aortic stenosis but not in interrupted aortic arch or coarctation subgroups, whereas they increased in pulmonary atresia but not pulmonary stenosis or tetralogy of Fallot subgroups compared with normal group ( P <.05). There was no significant difference in CPR between any study group or subgroup and normal control group. Conclusions: Our study suggests MCA‐PI is lower in aortic stenosis and high in pulmonary atresia but not significantly different in other LSOL, HLHS, RSOL, and HRHS. MCA‐PI regulation in CHD is probably more associated with left and right outflow obstruction, location of the obstruction, and hemodynamics rather than "brain sparing effect" or preferential shunting of blood to the fetal brain, heart, and adrenals in the stressed fetus (eg, IUGR). CPR may not be a sensitive measure for the effect of CHDs and their severity on cerebral and placental circulation.